Facebook : the Effects of Self-Esteem and Self Disclosure on Facebook. - Miller, Jules; Sulerud, Kyle; Schuett, Steven; Willkom, Bryan; Dworski, Jana; Nyberg, Luke (My University, 2009)
This study examined the amount of participant-reported self-disclosure on Facebook, particularly as it relates to participants' self-esteem.
Facebook : the Effects of Self-Esteem on Disclosre
Color poster with text and graphs describing research conducted by Jules Miller, Kyle Sulerud, Steven Schuett, Bryan Willkom, Jana Dworski, and Luke Nyberg, advised by Martha Fay.
Keywords: Self-esteem; Self-disclosure--Psychological aspects; Facebook (Internet resource); Posters